Chinese energy futures and their implications for the United States - Eberling, George; ProQuest (Firm) (Lanham, Md. : Lexington Books, 2011)
"Shows how China will most likely address its growing oil energy dependence. Eberling's study uses scenario analysis and the PRINCE model to determine what will be the most likely U.S. foreign policy consequences, stemming from the most current literature available on energy security and foreign policy. Chinese Energy Futures also contributes to the literature on Chinese and United States energy security, foreign policy, political economy, and political risk analysis."--Publisher's description.
The competitive dependency scenario -- The Asia-Pacific -- Central Eurasia -- The Middle East and North Africa -- Sub-Saharan Africa -- Western Europe -- Western hemisphere -- Summary -- The surplus scenarios : competitive versus cooperative -- Conclusions.
Includes bibliographical references (p. [159]-170) and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Petroleum industry and trade -- China; Energy security -- China; China -- Foreign economic relations -- United States; United States -- Foreign economic relations -- China; Electronic books